Ondo State University Ado-Ekiti Nigeria (Ondo, Nigeira : Ondo State University Ado Ekiti, 1986)
This book gives the full history and description of the Ondo State University of Ado-Ekiti.
Handbook 1986 / 88
hza 01/02/2019
Loans
Keywords: University prospectus; University regulation; Deans of faculty; Members of council; Nigeria